A Review of Plant Practice at Endako Mines - J. D. Wright; R. Woods (Society for Mining, Metallurgy & Exploration, 1976)
INTRODUCTION The Endako deposit was first explored in 1926, but development waited until the early nineteen sixties. It first came under the control of Placer Development in 1963, and early in 1964 a decision to bring it into production was reached. The deposit is located near the geographic center of British Columbia, and is served by an east-west communication system including a paved highway, mainline railway and good telephone, teletype, and computer facilities. The plant area is shown in Figure 1. The operation is known as the Endako Mines Division of Canex Placer Limited of Vancouver. First production was achieved in June, 1965, at a nominal rate of 10,000 tons per day, but it soon was closer to 15,000 tons per day. In 1967, two new grinding and flotation sections brought capacity to the present rate of approximately 27,000 tons per day. With mill heads of around 0.15 percent MoS2, production is about 14,000,000 pounds of molybdenum per year. A flowsheet of the operation is given in Figure 2. A legend for this flowsheet is given in Table 1. Published ore reserves are estimated at 214,500,000 tons at an average grade of 0.143 percent MoS2. PRIMARY CRUSHING The 85 or 100-ton haulage trucks dump over a grizzly into a 42 inch x 65 inch C.A.C. (Canadian Allis Chalmers) gyratory crusher.